The impact of leadership style on employee turnover and retention, and mediating job satisfaction and organization commitment - Ab Hamid, Kamal; Pahi, Munwar Hussain; Qureshi, Muhammad Asif; Arshad, Imran (2014)
In light of competitive pressure, increasing financial performance and competitiveness in the organizations, employee’s retention plays an important role.This paper aims to review the existing literature and propose a model on employee’s retention for better understanding the critical factors that helps to increase the employee’s retention.Extensive literature has been reviewed to find relationship between leadership style and employee’s retention and identified significant determinants of employee’s retention in an organization.Review of literature indicated that transformational leadership and transactional leadership has positive relationship with employee’s retention.Transformational leadership and transactional leadership have positive relationship with job satisfaction and organizational commitment. It also indicated that there is positive relationship exists between job satisfaction and organizational commitment. Moreover there is positive relationship exists between job satisfaction, organizational commitment and employee’s retention. From review of literature it is also highlighted that, there is dearth of literature on leadership styles and employee’s retention.This paper contributes in the existing knowledge by proposing mediating role of job satisfaction and organizational commitment between transformational leadership, transactional leadership and employee’s retention.The proposed model will help to better understand the relationship between transformational leadership, transactional leadership and employee’s retention.